(untitled) (Wudil Journal of Science and Technology Education, 2025)
With evidence of decrease in efficient flow portraying induced discharge flow pattern at signalized intersections mainly due to the drivers behaviours, the research provides empirical evaluation into the most conspicuous behaviours especially phone distractions and traffic violations along the subject approaches of three distinct signalized intersections within Kano Metropolis along three dual three-lane motorways. The research employed field observational method to assess the impacts of drivers’ behavior of cell-phone usages and traffic violations through green duration. It was observed after analysis; the highest distractive behaviour by drivers is use of cell-phone gulping SLT of 0.3-0.5 seconds against 0.1- 0.8 seconds of other activities or more respectively, constituting more than half capacity loss of the traffic. The headway of the traffic is impacted by an increase in 1 seconds for a single cell-phone user which posed a stabilizing effect with varying increase of 0.3 seconds when other any mix of activities are added. This concludes a variety of driver behavior having impact in different manner on the integrity of the traffic. The models provided may help researchers, practitioners, and policy makers among other stakeholders in formulating and employing various interventions and strategies to a more cordially, safe, effective and efficient traffic operations within and beyond signalized intersections. Better signal timing and social intervention is recommended to be appropriated. Whilst the data collection methodology and modeling should be minutely extended which would enhance the results along with other relevant researches.